Antidepressant-induced burning mouth syndrome: A case report - Alaa Alesa; Wid Kattan; Abdulhadi Albadri (SAGE Open Medical Case Reports, 2023)
Burning mouth syndrome is a chronic condition characterized by oral pain in the absence of intraoral clinical signs. The pathogenesis and etiology of burning mouth syndrome are not fully understood. Both men and women of all ages are at risk of developing this syndrome, but women are at an even higher risk. The management of burning mouth syndrome usually consists of the use of antidepressants. In this case report, we present a case of a 75-year-old lady who presented to the psychiatric clinic for management of her depressive symptoms. She was prescribed escitalopram and her dose was later increased. She then started experiencing a burning sensation in her mouth. She was seen by dental, medical, and psychological specialties regarding her symptoms. After careful historical and clinical evaluation, she was finally diagnosed with antidepressant-induced burning mouth syndrome. Antidepressant-induced burning mouth syndrome is a rare but very important condition to recognize. It has a huge effect on patients’ quality of life. The management of patients with antidepressant-induced burning mouth syndrome needs the involvement of a multidisciplinary team. Further high-quality studies are needed to help healthcare professionals better approach such patients.